Technical training of qualified athletes , specializing in the high jump with a running start, with additional funds - Gusarevich, A.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : To improve the process of technical training of qualified athletes, specializing in the high jump with a running start on the basis of additional funds. Material : The study involved 12 athletes qualified I sports category and candidate masters age 18-20 years. Number of attempts varied from 12-15, depending on the degree of fatigue study. Determined the effect of electrical stimulation on muscle groups leading the kinematic and dynamic characteristics of the runway and repulsion, as well as athletic performance. Results : It was established that the integrated use of electrical stimulation affects more effectively to improve the biomechanical characteristics of high jump and effectiveness than using electrical stimulation during takeoff and repulsion separately. Conclusions : On the basis of the experimental data we can recommend the use of complex electrical, as an additional means for improving technical skills and improve performance athletes qualified.